Grafting of Fatty Acids on Polyvinyl Alcohol: Effects on Surface Energy and Adhesion Strength of Acrylic Pressure Sensitive Adhesives - Germek, Eva; Schmid, Markus; Lindner, Martina (Frontiers in Materials, 2020)
Chemical grafting with fatty acid chlorides is known to reduce the surface tension of polymer substrates. The aim of this study was to evaluate the effect of different grafting parameters on functional properties such as the surface tension of grafted substrates and adhesion of acrylic pressure sensitive adhesives (PSA) on those substrates in dependence of storage time. There-fore, two substrates, paper and polyethylene terephthalate (PET), were coated with polyvinyl alcohol (PVOH). The PVOH showed similar degrees of hydrolysis but different molecular weights. Fatty acid chlorides (palmitoyl chloride, stearoyl chloride) were grafted on pure PET, pure paper, PVOH coated paper, and PVOH coated PET. On these samples, roughness was measured and peel strength and surface energy were determined over storage time. Peel strength was observed to increase with roughness. The chain length of fatty acid chlorides and storage time did not majorly influence peel strength.